Journal of Superconductivity and Novel Magnetism - Wolf, Stuart A.; Kresin, Vladimir Z.; Awana, V.P.S.; Felner, Israel; Ovchinnikov, Sergei; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Superconductivity and Novel Magnetism serves as the international forum for the most current research and ideas in these fields. This highly acclaimed journal publishes peer-reviewed original papers, conference proceedings and review articles that examine all aspects of the science and technology of superconductivity, including new materials, new mechanisms, basic and technological properties, new phenomena, and small- and large-scale applications. Novel magnetism, which is expanding rapidly, is also featured in the journal. The journal focuses on such areas as spintronics, magnetic semiconductors, properties of magnetic multilayers, magnetoresistive materials and structures, magnetic oxides, etc. Novel superconducting and magnetic materials are complex compounds, and the journal publishes articles related to all aspects their study, such as sample preparation, spectroscopy and transport properties as well as various applications.
Keywords: Condensed matter; Superconductivity; Superconductors; Magnetism; Magnetic materials; Materials science; Strongly Correlated Systems, Superconductivity; Magnetism, Magnetic Materials; Condensed Matter Physics; Characterization and Evaluation of Materials